Narrative Review of The Effectiveness of Rolling Massage and Endorphin Massage on ASI Production in Breastfeeding Mothers - Aprila, Prety Zinta; Hardisman, Hardisman; Yulizawati, Yulizawati (Universitas Andalas, 2023)
Background: World Health Organization (WHO) in 2020 stated that 149.2 million children under 5 years old are affected by stunting. National Statistics Center of Indonesia (BPS) stated that 5.2% of child under 2 years were in underweight condition and 1.2% of them were very underweight. Based on Indonesian Health Ministry Regulation (No. 23 of 2014), efforts to implement balanced nutrition to overcome chronic nutritional problems can be done through exclusive breastfeeding. Besides that, in 2020, West Sumatra province experienced a decrease in the percentage of breastfeeding from (77.6%) to (69.7%), which was caused dominantly by factor decreased of breast milk production and secretion by 32%. WHO states that there are 10 steps for successful exclusive breastfeeding, one of which is breast care, that can be achieved by giving of rolling massage and endorphin massage, which not many people know about.Purpose: The aim of this literature study is to present information about the application of rolling massage and endorphin massage as a way to accelerate and increase breast milk production.Methods: This research method was a literature review study. Journal searches were carried out by applying online database such as Pubmed, Garuda Portal, ScienceDirect and Google scholar. Articles were selected based on inclusion and exclusion criteria.Results: The analysis was carried out on 22 research articles. It was found that Rolling massage and endorphin massage are non-pharmacological techniques for breast care performed on the mother's back, neck and arms to trigger the excretion of the hormones prolactin and oxytocin.Conclusion: The influence of rolling massage and endorphin massage is useful in overcoming breast milk production constraintsKeywords: breastfeeding, breast milk, rolling massage, endorphin massage, breast care